Asset sales, firm performance, and the agency costs of managerial discretion - Lang, Larry; Poulsen, Annette; Stulz, René (Journal of Financial Economics, 1995)
We argue that management sells assets when doing so provides the cheapest funds to pursue its objectives rather than for operating efficiency reasons alone. This hypothesis suggests that (1) firms selling assets have high leverage and/or poor performance, (2) a successful asset sale is good news, and (3) the stock market discounts asset sale proceeds retained by the selling firm. In support of this hypothesis, we find that the typical firm in our sample performs poorly before the sale and that the average stock-price reaction to asset sales is positive only when the proceeds are paid out.